2017
DOI: 10.3390/nu9060561
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Inflammatory Diseases and Green Tea Polyphenols

Abstract: Chronic inflammatory diseases affect millions of people globally and the incidence rate is on the rise. While inflammation contributes to the tissue healing process, chronic inflammation can lead to life-long debilitation and loss of tissue function and organ failure. Chronic inflammatory diseases include hepatic, gastrointestinal and neurodegenerative complications which can lead to malignancy. Despite the millennial advancements in diagnostic and therapeutic modalities, there remains no effective cure for pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 71 publications
2
37
0
Order By: Relevance
“…To further analyze the anti-inflammatory action of In-OC in response to EGCG treatment, the epithelial as well as myofibroblast-mediated release of immune mediators IL-10 was measured. IL-10 secretion was upregulated after EGCG treatment, as reported in Figure 5d, establishing the mucosal protection (Oz, 2017) that confirms the anti-inflammatory effects of EGCG-treated compared with the untreated samples. Finally, as is known, EGCG was also a potential anti-fibrotic agent due to its attenuating effect on potential fibrotic markers (Sriram, Kalayarasan, & Sudhandiran, 2009).…”
Section: The Cross Section Image and 3d Reconstruction Of 3d-hie Growsupporting
confidence: 79%
“…To further analyze the anti-inflammatory action of In-OC in response to EGCG treatment, the epithelial as well as myofibroblast-mediated release of immune mediators IL-10 was measured. IL-10 secretion was upregulated after EGCG treatment, as reported in Figure 5d, establishing the mucosal protection (Oz, 2017) that confirms the anti-inflammatory effects of EGCG-treated compared with the untreated samples. Finally, as is known, EGCG was also a potential anti-fibrotic agent due to its attenuating effect on potential fibrotic markers (Sriram, Kalayarasan, & Sudhandiran, 2009).…”
Section: The Cross Section Image and 3d Reconstruction Of 3d-hie Growsupporting
confidence: 79%
“…Dietary antioxidants protect against inflammation caused by oxidative stress. Antioxidants such as flavonoids in green tea may decrease inflammatory response through scavenging free radicals and inhibiting nuclear factor‐κB as oxidant‐sensitive transcription factors (Mitjavila & Moreno, ; Oz, ).…”
Section: Introductionmentioning
confidence: 99%
“…Of these, EGCG is the most abundant catechin in green tea [6]. Numerous reports have demonstrated that the green tea polyphenol EGCG is a potent antioxidant that plays an important role in inhibiting inflammation [7,8]. In our previous study, we showed that EGCG suppressed tumour necrosis factor-α (TNF-α)-induced monocyte chemoattractant protein-1 (MCP-1) expression in human umbilical vein endothelial cells (HUVECs) [9].…”
Section: Introductionmentioning
confidence: 99%